Efficacy of Trimethoprim and Sulfamethoxazole in the Prevention and Treatment of Pneumocystis carinii Pneumonitis - Hughes, Walter T. (1974)
A combination of trimethoprim and sulfamethoxazole was effective in the prevention and treatment of Pneumocystis carinii pneumonitis in cortisonetreated rats. Although all of 15 untreated rats died with P. carinii pneumonitis, none of 15 given trimethoprim-sulfamethoxazole prophylactically acquired the infection. After P. carinii pneumonitis was established, 9 of 14 rats recovered after treatment with trimethoprim-sulfamethoxazole compared with only 2 of 14 treated with pentamidine isethionate. Rifampin and clindamycin, separately or in combination with pentamidine, were ineffective in the prevention and treatment of P. carinii infection.